A phantom ultrasonic insect chorus repels low‐flying bats, but most are undeterred - Sedlock, Jodi L.; Gomes, Dylan G. E.; Rubin, Juliette J.; Woody, Sarah; Hadi, Buyung A. R.; Barber, Jesse R. (Wiley, 2021)
The acoustic environment can serve as a niche axis, structuring animal behaviour by providing or obscuring salient information. Meadow katydid choruses occupy the ultrasonic, less studied, realm of this acoustic milieu, form dense populations in some habitats and present a potential sensory challenge to co‐occurring ultrasonic‐hearing animals. Aerial‐hawking insectivorous bats foraging immediately over vegetation must listen for echoes of their prey and other cues amidst the chorus din. We experimentally created the cacophony of a katydid chorus in a katydid‐free rice paddy using an aggregation of 100 ultrasonic speakers in a 25 × 25 m grid to test the hypothesis that aerially hawking bats are averse to this noise source. We alternated between chorus‐on and chorus‐off hourly, and acoustically monitored bat activity and arthropod prey abundance. We found that our phantom katydid chorus reduced bat activity nearest the sound source by 39.3% (95% CI: 7.8%–60.0%) for species whose call spectrum fully overlapped with the chorus, and elicited marginal reductions in activity in species with only partial spectral overlap. Our study suggests that ultrasonic insect choruses degrade foraging habitat, potentially suppressing bats’ ecosystem services as consumers of pests; and, given the global distribution of meadow katydids, may provide an underappreciated force modifying animal behaviour in other grassland habitats.The acoustic environment can serve as a niche axis, structuring animal behaviour by providing or obscuring salient information. Meadow katydid choruses occupy the ultrasonic, less studied, realm of this acoustic milieu, form dense populations in some habitats and present a potential sensory challenge to co‐occurring ultrasonic‐hearing animals. Aerial‐hawking insectivorous bats foraging immediately over vegetation must listen for echoes of their prey and other cues amidst the chorus din.We experimentally created the cacophony of a katydid chorus in a katydid‐free rice paddy using an aggregation of 100 ultrasonic speakers in a 25 × 25 m grid to test the hypothesis that aerially hawking bats are averse to this noise source. We alternated between chorus‐on and chorus‐off hourly, and acoustically monitored bat activity and arthropod prey abundance.We found that our phantom katydid chorus reduced bat activity nearest the sound source by 39.3% (95% CI: 7.8%–60.0%) for species whose call spectrum fully overlapped with the chorus, and elicited marginal reductions in activity in species with only partial spectral overlap.Our study suggests that ultrasonic insect choruses degrade foraging habitat, potentially suppressing bats’ ecosystem services as consumers of pests; and, given the global distribution of meadow katydids, may provide an underappreciated force modifying animal behaviour in other grassland habitats.A free Plain Language Summary can be found within the Supporting Information of this article.